Sikap Inggris terhadap Indonesia menjelang pertempuran Surabaya 1945 - I Basis Susilo (Masyarakat, Kebudayaan dan Politik, 2017)
This article discusses the difference of British Government decision maker's behavior towards Indonesia since Indonesian independence until the battle of Surabaya, 10 November 1945. There are two assumptions underlying this paper: (1) that behavioural differences are frequently happened and create crises and problems, and (2) that the differences rise were based on interests and each party’s capacity that measured by the law of A=f-I&C (Attitude is the function of Interest & Capability). Based on that assumptions, this article proposes two hypotheses: (1) that the Battle of Surabaya was initialized with differences of attitudes taken by the British decision makers. and (2) that the differences were shaped by the realities they were dealing with. This paper focuses on attitudes toward: (1) the task of the British force in the Netherlands East Indies, and (2) the need to confer with the Indonesian leaders. The findings are; not only decision maker’s behaviour were different, they also dynamic depending on how they defined circumstances and development of events in Indonesia, in Netherlands, and international affairs.